Adoption of green electricity by small- and medium-sized enterprises in Germany. (June 2016) - Rahbauer, Sebastian; Menapace, Luisa; Menrad, Klaus; Decker, Thomas
Abstract: Since the liberalization of the German electricity market in 1998, green electricity (GE), i.e. electricity produced from environmentally friendly sources and marketed as such, has been available to German customers. Nonetheless, the demand for GE has remained low among the biggest electricity customer group in Germany, namely small- and medium-sized enterprises (SMEs). Based on an extensive review of the literature, this article provides a synthesis of existing empirical findings related to GE adoption in German SMEs. In addition to the literature directly addressing GE adoption, the literature on green practices, green supply chain management, corporate environmental responsibility and energy efficiency was reviewed. This article lays the groundwork for a theoretical model that reflects the decision of German SMEs to adopt GE by identifying adoption factors and resulting barriers. GE adoption factors are organized into four purchase-related factor groups and two sales-related factor groups. Purchase-related factors relate to the entrepreneur's personality, the technical systems, economic aspects, and the SME's characteristics. Sales-related factors relate to sales markets and green marketing. The examined literature on industrial GE adoption demonstrates the importance of ' altruistic motives ' for GE adoption in SMEs. The main barriers identified by the remaining literature were (1) lack of knowledge regarding the GE system reliability, (2) upward-biased perceptions of GE price premiums and (3) lack of communicability of GE usage in the manufacture of products to customers. The article closes with recommendations for promoting GE adoption among SMEs. Based on the three main barriers identified, instruments well-suited to promote GE adoption include an online register for GE tariffs that provides SMEs with information regarding GE providers, prices and switching procedures and a standardized label that allows SMEs' customers to identify products manufactured using GE.